Potential eco-friendly Zinc Oxide nanomaterials through Phyco-nanotechnology –A review. (August 2021) - Vijayakumar, S.; Vidhya, E.; Nilavukkarasi, M.; Punitha, V.N.; Praseetha, P.K.
Abstract: The physico-chemical methods of synthesizing the nanoparticles which are expensive and involve harmful substances are exuded to the environment. Hence, green synthesis of nanoparticles with low cost, non-toxic and eco-friendly advances currently into new research. Amidst the metal oxides, ZnO nanoparticles are synthesized using various biological species that have tremendously increased for various applications. This review details on algae intervened synthesis of ZnO nanoparticles used for numerous biological applications such as antimicrobial, cytotoxicity, antioxidant, larvicidal, and photocatalytic activities. Highlights: Synthesis of ZnO nanoparticles using various algal extract. Shape and size of the nanoparticles were reported using various characterizations. Various biological applications were included in this review article.